Heat Integration Improvement for Benzene Hydrocarbons Extraction from Coke-Oven Gas - Tovazhnyanskyy, Leonid Leonidovich; Kapustenko, P. O.; Ulyev, L.; Boldyryev, S. A. (The Italian Association of Chemical Engineering, 2011)
In present work the extraction of benzene hydrocarbons from coke-oven gas on the one column unit is studied. Energy consumption of the investigated plant is defined and disadvantages of existing heat exchangers network are shown. The integrated flexible flowsheet is proposed based on process integration method. It enables to reduce both hot and cold utilities consumption on 2,872 kW with pay back period about 9 months.